(3GdeWdYs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj efM CMHJg HGddWa hGdJhajb agPG TQM dcJGH GdYdGeI CKjQ GdOjf GdCHgQj GdeSei HEjSGZhLj aj Yde GdefWb jMd CdaGXg hjHjf eQGOg hjaJM eZdbg hjbjO eWdbg s
(3BNQgG (B:s
(3hGdJeKjd hgh GKHGJ Mce hGQO LRA BNQ deYfi eTJQc HjfgeG hGdabgGA jSehfg bjSGSG dKHhJg aj QLRA BNQ hGdYeOI Cj eG jYJeO Ydjg ef gPg GdbjGSGJ gh GdHQgGf dJQcHg ef GdebOeGJ GdjbjfjI hdchfg cGajG aj GMJSGH GdYdhe GdJUOjbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3/46s
(3cTa GdXfhf (B1/208s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs